Individual Rights and the Making of the International System / [electronic resource] - Reus-Smit, Christian (Cambridge : Cambridge University Press, 2013)
We live today in the first global system of sovereign states in history, encompassing all of the world's polities, peoples, religions and civilizations. Christian Reus-Smit presents a new account of how this system came to be, one in which struggles for individual rights play a central role. The international system expanded from its original European core in five great waves, each involving the fragmentation of one or more empires into a host of successor sovereign states. In the most important, associated with the Westphalian settlement, the independence of Latin America, and post-1945 decolonization, the mobilization of new ideas about individual rights challenged imperial legitimacy, and when empires failed to recognize these new rights, subject peoples sought sovereign independence. Combining theoretical innovation with detailed historical case studies, this book advances a new understanding of human rights and world politics, with individual rights deeply implicated in the making of the global sovereign order.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).